Soft-Sediment Communities of the Northern Indian River Lagoon, FL, United States - Lunt, Jessica; Freeman, Christopher J.; Janiak, Dean S.; Bayliss, Katrina; Stephens, Michelle; Galimany, Eve; Paul, Valerie J. (Frontiers in Marine Science, 2021)
Understanding the structure and function of infaunal communities is useful in determining the biodiversity and ecosystem function of shallow estuaries. We conducted a survey of infaunal communities within three separate water basins (Mosquito Lagoon, Indian River, and Banana River) in the larger northern Indian River Lagoon, Florida to establish a database of infaunal community structure and function. Twenty-seven sites were sampled quarterly from 2014-2016. Analysis of all samples determined that basin, season, and sediment composition were the primary drivers of macrobenthic community composition. Diversity was highest in the Mosquito Lagoon, and lower in spring compared to other seasons. The occurrence of a brown tide (Aureoumbra lagunensis) in 2016 allowed a comparison of winter and spring communities before (2015) and during (2016) a bloom event. Community composition and diversity at the Banana River sites were the most affected by the bloom event with the lowest diversity and abundances during the bloom. Diversity in the Indian River was also lower during the bloom, while the Mosquito Lagoon was unaffected by the bloom. Species of all feeding groups were affected by the bloom, with lower abundances found in all groups. In addition, to determine the overall trophic diversity of infaunal communities, we collected infaunal organisms from two of the quarterly-sampled sites for isotope analyses. Values for δ13C and δ15N isotopes of infaunal tissue were compared to those of potential food sources at each site. Substantial interspecific variation in isotope values of infaunal organisms within a site suggests the presence of diverse nutritional modes that include suspension and deposit feeding and predation. Together, these data suggest that infaunal communities contribute to benthic pelagic coupling and nutrient cycling within the estuarine communities, but the overall function of these communities may be tightly linked to their species composition.